Knowledge, Attitude, and Practice Survey of COVID-19 Among Healthcare Students During the COVID-19 Outbreak in China: An Online Cross-Sectional Survey - Zhang, Juxia; Yin, Yuhuan; Dean, Judith; Zhang, Xiaoli; Zhang, Yiyin; Wang, Jiancheng; Zhang, Yinping (Frontiers in Public Health, 2021)
Background: The ongoing coronavirus disease (COVID-19) outbreak has placed the healthcare system and student training under considerable pressure. However, the plights of healthcare students in the COVID-19 period have drawn limited attention in China. Methods: A cross-sectional on-line survey was undertaken between January and March 2020 to explore the COVID-19 knowledge, attitude, and practice (KAP) survey among Chinese healthcare students. Demographic information and data on KAP were obtained using a self-reported questionnaire. The percentage KAP scores were categorized as good or poor. Independent predictors of good knowledge of COVID-19 were ascertained to use a logistic regression model. Results: Of the 1,595 participants, 85.9% (1,370) were women, 53.4% were junior college students, 65.8% majoring in nursing, and 29.8% had received training on COVID-19. The overall median percentage for good KAP was 51.6% with knowledge of 28.3%, attitude 67.8%, and practice 58.6%, respectively. Independent predictors of good knowledge of COVID-19 were being students ≥25 (95% CI = 0.27–0.93, P = 0.02), those taking bachelor degrees (95% CI = 1.17–2.07, P = 0.00), and those having participated in COVID-19 treatment training. Conclusions: The result of this study revealed suboptimal COVID-19-related KAP among healthcare students in China. To effectively control future outbreaks of COVID-19, there is a need to implement public sensitization programs to improve the understanding of COVID-19 and address COVID-19-related myths and misconceptions, especially among healthcare students.